(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the outpatient treatment patterns at the University Medical Center Ho Chi Minh City – Campus 3 after the establishment of specialized clinics. This study aimed to characterize the prevalence of integrative Traditional Medicine (TM) – Western Medicine (WM) models, pharmacological prescription profiles, and the distribution of non-pharmacological therapies. Methods: A descriptive cross-sectional study was conducted using 21,525 eligible electronic medical records from outpatient visits between April 1, 2024, and March 31, 2025. The unit of analysis was each outpatient visit. Data on integrative treatment patterns, pharmacological prescriptions, and non-pharmacological therapies were collected. Descriptive statistics were used to calculate frequencies and percentages. Results: Of 21,525 outpatient visits, the integrative TM-WM model was the most prevalent pattern (50.82%). TM drugs were prescribed in 87.20% of visits (with finished products predominating at 70.80%), while WM drugs were prescribed in 54.41%. The most common WM drug group was cardiovascular drugs (23.86%); the most common TM herbal categories were Qi tonifying (17.58%) and blood tonifying (11.71%). TM procedures accounted for the majority of non-pharmacological therapies (64.59%), led by thread embedding acupuncture (23.38%) and electroacupuncture (10.14%). Conclusion: The outpatient treatment model at the specialized clinics is highly integrative, characterized by the modernization of TM drug use, pharmacological coordination between TM and WM, and a foundational reliance on evidence-based non-pharmacological TM therapies. These findings provide a basis for optimizing clinical protocols, health policy planning, and future research in integrative medicine.